Explore the theoretical basis and implementation strategy of low-carbon Urban Community Planning - Yu, Yan (Frontiers in Environmental Science, 2022)
Cities carry out various human production and living activities, consume a lot of carbon energy, become the main source of greenhouse gas emissions, and have an increasing impact on the climate. Therefore, as the main battlefield of carbon emission management, cities have become the focus of low-carbon research.The concept of a "low-carbon city" appears in dealing with global climate change. In order to further study the application of low carbon cities, this research discusses how to achieve the goal of low carbon cities from low carbon communities by introducing the concept of low carbon cities and the planning views of experts and scholars on low carbon cities, and based on the theoretical research and practical experience of low carbon cities. In the course of the study, Qianhai Cooperation Zone and Bao'an Central District in Shenzhen are introduced as case studies to analyze the practical application of low-carbon city construction. Through this study, we found that the purpose of low-carbon cities is to provide physical space for resource savings, low waste emissions, high operating efficiency, green and sustainable urban activities. For the completely dispersed urban structure in some regions of China, the polycentric network structure is a favorable urban structure for these regions to achieve low carbon and efficient development. The polycentric network cities have high urban density and activity intensity, so corresponding low-carbon strategies can be effectively implemented according to different functional positioning, density and activity density. On the other hand, in order to achieve efficient and low-carbon urban development, the community should be the basic unit. Only when low carbon is realized in the community can the basic low carbon of urban life be guaranteed and the low carbon of the whole city be realized.